Concord errors in postgraduates' dissertations and theses (2016)
The concept ‘concord’, which signifies agreement between the different elements that are used in a sentence, has been extensively discussed by scholars. It has usually been assumed that concord only poses problems for secondary school students and undergraduate students in tertiary institutions. Postgraduate students are thought to be immune to this problem. This paper examined the dissertations of eight postgraduate students in Linguistics Department, University of Ibadan with the aim of either substantiating or debunking this claim. Forty-six sentences are extracted from five master’s projects, one M.Phil dissertation and two Ph.D theses. The basic concept of Error Analysis which is a key element of the systemic grammar formed the theoretical basis of this work. Grammatical errors as a result of poor mastery of the rules of concord are responsible for these forty-six faulty constructions. These errors could broadly be classified into two – grammatical and notional. Most of them result from lack of agreement between the subject and verb, pronouns and antecedents, demonstratives and nouns, articles and nouns, the use of the copula ‘is’ and the auxiliary ‘have’ which do not agree with the subjects of the sentences in which they are used. Postgraduate students are not immune to the problem of concord. Thus, the researcher recommends that the teaching of the General Studies Programme ‘Use of English’ at the undergraduate level should be intensified and that a similar course should be introduced at the postgraduate level to complement what is taught at the undergraduate level to improve the quality of the use of English of undergraduate and graduate students